Perceived spiritual brand attributes of Islamic banking institutions in Malaysia - Ab Hamid, Siti Ngayesah; Wan Jusoh, Wan Jamaliah; Maulan, Suharni (2018)
For Muslims, an Islamic brand does not only concern on halal and haram or on shari’ah compliance, but is part of a belief system. It cannot be separated from faith and should take into consideration the spiritual needs of the Muslim target consumers which based their actions on pleasing The Creator. Based on these, several proposals have been written on the spiritual aspect of an Islamic brand. However, only few studies could be found trying to understand its underlying dimensions. This study explores the dimensions and components of an Islamic brand spiritual attributes specifically in the context of an Islamic bank. Using a purposive sampling technique, semi-structured interviews were conducted with 16 individuals of various backgrounds including Islamic banking managers, shari’ah advisors, academicians, and customers. Three main themes were identified which are ethics, corporate social responsibility (CSR) and beliefs. The findings contribute theoretically to the Islamic branding literature by proposing new underlying dimensions and components mainly focusing on the spiritual aspect. Financial service providers could consider these dimensions in the process of creating strategic competitive position.